Dietary Quality Index and Cardiometabolic Risk Factors among Adult Women - Behzad Zamani; Elnaz Daneshzad; Manije Darooghegi Mofrad; Nazli Namazi; Bagher Larijani; Nick Bellissimo; Leila Azadbakht (Tehran University of Medical Sciences, 2021)
Background: The prevalence of cardiovascular disease is dramatically increasing particularly in developing countries. Among the different factors, diet has an important role in the pathogenesis of these diseases. This study aimed to assess the relationship between dietary quality index-international (DQI-I) and cardiovascular risk factors in adult Iranian women. Methods: This was a cross-sectional study of 371 participants, aged 20-50 yr, and recruited from 10 health centers from health centers affiliated with Tehran University of Medical Sciences (TUMS), Tehran, Iran in 2018. Usual dietary intake was evaluated by a validated and reliable 168-items food frequency questionnaire (FFQ). To assess overall quality of diet, the Dietary Quality Index-International (DQI) was used. Anthropometric measurements, blood pressure, and fasting blood of samples were taken to assess biochemical parameters related to cardiovascular disease. Results: The results of linear regression showed that DQI-I score was inversely and directly associated with serum level of total cholesterol (TC) (0.27, confidence interval (CI): 0.13-0.58; P<0.001) and high-density lipoprotein cholesterol (HDL-C) (2.53, CI: 1.42-4.52; P=0.001), respectively. However, there was no significant association between DQI-I and other cardiovascular risk factors. Conclusion: A greater DQI-I score was associated with preferable lipid profile including TC and HDL-C. Future large-scale, prospective cohort or clinical studies are required to confirm these findings.